PROCESSOS DE APROPRIAÇÃO DE LEITURA E ESCRITA DE CRIANÇAS COM DEFICIÊNCIA INTELECTUAL: UMA APOSTA NA MEDIAÇÃO PEDAGÓGICA - Nascimento, Alice Pilon do (2021)
This doctoral research analyzed the processes of appropriation of reading and writing skills of students with intellectual disabilities enrolled in the literacy cycle of a common school in the municipal teaching network of Vitória city, in 2019. Studying the appropriation of reading and writing has been a great challenge in education, given the number of students who have not appropriated this knowledge, whose primary role is the humanization process. The study was based on the perspectives of historicalcultural psychology and historical-critical pedagogy, assuming the intentional and systematized character of teaching as a sine qua non condition for the learning and development of students. It focused on approaching the importance of the teaching method prepared by the historical-critical pedagogy, considering the processes of each student. Then, the need to comprehend the real and imminent development zone are basic principles for a educational work based on a pedagogical mediation. Intending to broaden the phenomenon's lens, this work produced an analysis of the National Education Plan with a view to discussing the Special Education – literacy interface. Anchored in an action-research, it allowed for a dialogic construction of the teaching practice so that children, especially those with disabilities, appropriated reading and writing. Students with the same diagnosis were at different times with regard to learning and development. Hence, it was decided to base the teaching on the development of psychological functions called "prehistory of writing" with one student and with the other a more directive action for the development of writing and reading skills. It is seen that students needed more systematic pedagogical investments to achieve the objective. It is observed that, compared to what is experienced at school, the adult is configured as an important focus in the students' processes, however, the participation of the peer, of classmates, is also evident. With a view to achieving this goal, the study debates the need to strengthen the articulation of Special Education professionals with teachers. For this last topic, questions referring to continuing education were raised, as well as teaching working conditions. The work links the advance in the development of more elaborate psychic functions as Reading and writing to three movements. The first focuses on the need to develop other psychic functions – in a dialectical perspective – such as language, perception and voluntary attention. The role of the teacher throughout the process is taken as a basis. And finally, the action of the State is crucial, with ways to guarantee working conditions and public policies. The three topics must interlock dialogically.